A Framework for Optimizing Technology-Enabled Diabetes and Cardiometabolic Care and Education: The Role of the Diabetes Care and Education Specialist. Issue 4 (August 2020) - Greenwood, Deborah A.; Howell, Fran; Scher, LaurieAnn; Yousef, Gretchen; Rinker, Joanne; Yehl, Kirsten; Isaacs, Diana; Peeples, Malinda M.
Purpose: The purpose of this article is to present a framework for optimizing technology-enabled diabetes and cardiometabolic care and education using a standardized approach. This approach leverages the expertise of the diabetes care and education specialist, the multiplicity of technologies, and integration with the care team. Technology can offer increased opportunity to improve health outcomes while also offering conveniences for people with diabetes and cardiometabolic conditions. The adoption and acceptance of technology is crucial to recognize the full potential for improving care. Understanding and incorporating the perceptions and behaviors associated with technology use can prevent a fragmented health care experience. Conclusion: Diabetes care and education specialists (DCES) have a history of utilizing technology and data to deliver care and education when managing chronic conditions. With this unique skill set, DCES are strategically positioned to provide leadership to develop and deliver technology-enabled diabetes and cardiometabolic health services in the rapidly changing healthcare environment.